Producing "African" knowledge. Reflections from CODESRIA - (:unkn) unknown (My University, 2020)
African intellectual communities often remain unknown in the French academic world. This article examines the case of CODESRIA (Council for Social Science Research in Africa) whose knowledge remains confined to the circles of 'Africanists'. Such a lack of knowledge contrasts with the recognition given in the North to some of the individual work of scholars from the same geographical space. These contrasting dynamics of recognition refer back to the phantasmagorical figure of the "globalized intellectual" from the South and overlook the intellectual communities in which the trajectory of the actors concerned is or has been inscribed at a given time. Approaching "African" thinkers rather than the intellectual communities in which they are or have been involved casts a modest veil over debates initiated in their communities of origin. From this perspective, this article provides an overview of one institution, CODESRIA, as an actor in this intellectual community, and discusses the way in which the issue of the decolonisation of knowledge has been addressed there, taking the case of its last General Assembly.
Keywords: African Research